Biochemical changes due to root-knot nematode, Meloidogyne incognite (KOFOID AND WHITE) chitwood in ginger (Zingiber officinale Roscoe). - Sunilkumar B C (Department of Agricultural Entomology, College of Agriculture, 2016)
An experiment entitled “Biochemical changes due to root-knot nematode, Meloidogyne incognita (Kofoid and White) Chitwood in ginger (Zingiber officinale Roscoe)” was undertaken at Department of Agricultural Entomology, College of Agriculture, Vellayani, Thiruvananthapuram, during 2014-16. The main objective of the study was to assess the biochemical changes in ginger due to the infestation of M. incognita and to screen five important ginger varieties viz., IISR Mahima, IISR Rejatha, IISR Varada, Athira and Karthika against M. incognita. The study involved two pot culture experiments, both laid out in completely randomized design. First pot culture experiment was carried out in 30 cm diameter earthen pots by introducing four inoculum levels of M. incognita J2 (each replicated five times) ten days after planting. Six months after inoculation (MAI), biochemical analysis of rhizome and leaf samples were done. The result of the first pot culture experiment revealed that there was a progressive decrease in plant growth and yield parameters were observed with increase in inoculum levels of M. incognita at six MAI. The maximum reduction in plant height (38.38 per cent), fresh weight of shoot (43.03 per cent), dry weight of shoot (44.78 per cent), number of tillers (41.10 per cent) and rhizome yield (40.6 per cent) were observed in plants inoculated with 10,000 J2. The plant height, dry weight of shoot, number of tillers and the yield parameters decreased significantly in plants inoculated with 10,000 J2 compared to other levels and uninoculated plants. The plants inoculated with 10,000 J2 showed low pH (6.37) and EC (0.27 d S m-1) compared to the uninoculated plants and was significantly different from all other treatments. Defense enzymes viz., peroxidase (PO), polyphenol oxidase (PPO), phenylalanine ammonia lyase (PAL) of rhizome increased with increase in inoculum levels of M. incognita at six MAI. The plants inoculated with 10,000 J2 158 showed high phenol content (3.932 mg g-1 tissue), PO (8.82 changes in absorbance min-1 g-1 tissue), PPO (0.74 changes in absorbance min-1 g-1 tissue) and PAL (16.70 changes in cinnamic acid min-1 g-1 tissue) in rhizome compared to other treatments. Similar results were noticed in leaf samples as well. After harvest, the starch, protein, crude fibre, total ash and oleoresin content of rhizome decreased in plants inoculated with 500 J2 pot-1 onwards. The plants inoculated with 10,000 J2 showed low starch (12.78 per cent), protein (2.52 per cent), crude fibre (4.69 per cent), total ash (1.24 per cent), oleoresin content (3.518 per cent) compared to the uninoculated plants. The second pot culture experiment was carried out to screen five important ginger varieties against M. incognita. Minimum number of galls (28.6 plant-1) and gall index (3) was observed in the variety IISR Mahima and it was significantly different from other varieties. The variety Karthika was highly susceptible with a gall index 5 and varieties IISR Varada, IISR Rejatha and Athira were found to be susceptible (gall index 4) to M. incognita. However, variety IISR Mahima was found to be moderately resistant to M. incognita on the basis of gall index (3). The nematode population in soil, rhizome and root were minimum in IISR Mahima and maximum in case of variety Karthika. The lowest PO, PPO and PAL activity was observed in the case of variety Karthika. Based on the results of the study, it is concluded that there was a progressive increase in phenol content and defense enzymes viz. PO, PPO, PAL in both leaf and rhizome with increase in inoculum levels of M. incognita. Starch, protein, crude fibre, total ash, oleoresin content, pH and EC of rhizome decreased with increase in inoculum levels of M. incognita. The variety IISR Mahima showed more defense against M. incognita compared to other varieties due to higher PO, PPO, and PAL activity.